2020
DOI: 10.1002/advs.202001698
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Blue‐Emitting CsPbBr3 Perovskite Nanocrystals through Neodymium Doping

Abstract: Colloidal CsPbX 3 (X = Br, Cl, and I) perovskite nanocrystals exhibit tunable bandgaps over the entire visible spectrum and high photoluminescence quantum yields in the green and red regions. However, the lack of highly efficient blue-emitting perovskite nanocrystals limits their development for optoelectronic applications. Herein, neodymium (III) (Nd 3+) doped CsPbBr 3 nanocrystals are prepared through the ligand-assisted reprecipitation method at room temperature with tunable photoemission from green to deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 72 publications
7
98
0
Order By: Relevance
“…Most recently, there have been much more researches about perovskite QDs by composition engineering for wider optoelectronic applications. [68][69][70]…”
Section: Structure Of Perovskitementioning
confidence: 99%
“…Most recently, there have been much more researches about perovskite QDs by composition engineering for wider optoelectronic applications. [68][69][70]…”
Section: Structure Of Perovskitementioning
confidence: 99%
“…Their polyvalent states endow themselves with intriguing redox properties and unique luminous and electromagnetic characteristics. [ 41–45 ]…”
Section: Strategies For Preparing Cyan‐emitting Perovskitesmentioning
confidence: 99%
“…This is due to the following reasons: 1) the reduction of (lead or halogen) defects is attributed to the flexible redox properties of REE ion pairs (e.g., Eu 3+ –Eu 2+ ), [ 42 ] 2) the enhancement of the exciton binding energy resulting from the increased electron and hole effective masses, and 3) the increase in oscillator strength ascribed to the shortening of the Pb‐halogen bond. Xie et al [ 41 ] reported the preparation of CsPbBr 3 : x Nd 3+ NCs (where x is the atomic‐doping ratio x = Nd/(Nd + Pb)) by integrating Nd 3+ into CsPbBr 3 NCs as B‐site dopants. As shown in Figure a‐i, the emission peaks could be finely tuned from blue (459 nm) to cyan (484, 494, and 515 nm, Table 1 ) with the PLQY values in the range of 75–90% through Nd 3+ doping.…”
Section: Strategies For Preparing Cyan‐emitting Perovskitesmentioning
confidence: 99%
See 2 more Smart Citations